The Ultrastructural Study of Tumorigenic Cells Using Nanobiomarkers - Pavon, Lorena Favaro; Marti, Luciana Cavalheiro; Sibov, Tatiana Tais; Malheiros, Suzana M. F.; Oliveira, Daniela Mara; Guilhen, Daiane Donna; Camargo-Mathias, Maria Izabel [UNESP]; Amaro Junior, Edson; Gamarra, Lionel Fernel (Mary Ann Liebert, Inc., 2010)
Despite recent advances, patients with malignant brain tumors still have a poor prognosis. Glioblastoma (WHO grade 4 astrocytoma), the most malignant brain tumor, represents 50% of all astrocytomas, with a median survival rate of <1 year. It is, therefore, extremely important to search for new diagnostic and therapeutic approaches for patients with glioblastoma. This study describes the application of superparamagnetic nano-particles of iron oxide, as well as monoclonal antibodies, of immunophenotypic significance, conjoined to quantum dots for the ultrastructural assessment of glioblastoma cells. For this proposal, an immunophenotypic study by flow cytometry was carried out, followed by transmission electron microscopy analysis. The process of tumor cell labeling using nanoparticles can successfully contribute to the identification of tumorigenic cells and consequently for better understanding of glioblastoma genesis and recurrence. In addition, this method may help further studies in tumor imaging, diagnosis, and prognostic markers detection.
Keywords: cancer diagnosis; glioblastoma; immunolocalization; markers; nanoparticles; ultrastructural